2005
DOI: 10.1212/01.wnl.0000180407.15369.92
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion body myopathy and Paget disease is linked to a novel mutation in the VCP gene

Abstract: Mutations in the valosin-containing protein (VCP) on chromosome 9p13-p12 were recently found to be associated with hereditary inclusion body myopathy, Paget disease of the bone, and frontotemporal dementia (IBMPFD). We identified a novel missense mutation in the VCP gene (R159H; 688G>A) segregating with this disease in an Austrian family of four affected siblings, who exhibited progressive proximal myopathy and Paget disease of the bone but without clinical signs of dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
74
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 8 publications
0
74
0
1
Order By: Relevance
“…As such, the term IBMPFD seems overly restrictive. IBMPFD-ALS is similarly cumbersome and probably inadequate given the rare, but well-described, involvement of other organ systems including cardiac, 13 hepatic, 14 visual, 14 auditory, 15 sensory, 16 and autonomic systems, 17 as well as emerging evidence that mutations in VCP may infrequently manifest as Parkinson disease, [18][19][20] hereditary spastic paraplegia, 21 or cerebellar ataxia. 22 Instead, we propose to change the name of this syndrome from IBMPFD to multisystem proteinopathy (MSP), using the nomenclature of MSP1 for disease caused by mutations in VCP, MSP2 when due to mutations in HNRNPA2B1, 5 MSP3 when caused by HNRNPA1 mutations, 5 and MSP4 when due to mutations in the as yet unidentified gene.…”
Section: Resultsmentioning
confidence: 99%
“…As such, the term IBMPFD seems overly restrictive. IBMPFD-ALS is similarly cumbersome and probably inadequate given the rare, but well-described, involvement of other organ systems including cardiac, 13 hepatic, 14 visual, 14 auditory, 15 sensory, 16 and autonomic systems, 17 as well as emerging evidence that mutations in VCP may infrequently manifest as Parkinson disease, [18][19][20] hereditary spastic paraplegia, 21 or cerebellar ataxia. 22 Instead, we propose to change the name of this syndrome from IBMPFD to multisystem proteinopathy (MSP), using the nomenclature of MSP1 for disease caused by mutations in VCP, MSP2 when due to mutations in HNRNPA2B1, 5 MSP3 when caused by HNRNPA1 mutations, 5 and MSP4 when due to mutations in the as yet unidentified gene.…”
Section: Resultsmentioning
confidence: 99%
“…The mutated amino acids include R93C, R95C R95G, R155C, R155H, R155P, G157R, R159H, R159C, R191Q, L198W, A232E, T262A, and N387H (35)(36)(37)(38)(39). Except for Thr-262, all other mutations were not observed at serine, threonine, tyrosine, or lysine.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, about a dozen missense mutations in the human VCP gene have been identified as causing inclusion body myopathy with Paget disease of bone and frontotemporal dementia (IBMPFD), an autosomal dominant inherited disease that affects multiple tissues, including muscle, bone, and the cerebral cortex (35)(36)(37)(38)(39). Although it is now known that VCP is critically involved in the pathogenesis of several types of human disorders, including neurodegeneration, the detailed molecular mechanisms mediated by VCP in neurodegenerative disorders remain to be elucidated.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15] Recently, a study using whole exome sequencing identified a VCP mutation (p.R191Q) in a family in which some individuals presented clinically with amyotrophic lateral sclerosis (ALS). The frequency of VCP mutations in familial ALS (FALS) patients is estimated at approximately 2%.…”
mentioning
confidence: 99%